Pengelolaan Kelas dalam Pembelajara Fisika - Aito Aito; Rohiat Rohiat; Syaiful Anwar (UNIVERSITAS BENGKULU, 2018)
Abstract. The general purpose of this research was to describe in depth and comprehensive the clasroom management of physics learning class at Public Senior High School Number 1 West Pendopo Empat Lawang Regency. This research uses descriptive qualitative research method. The subjects of the study were principals, vice principals, teachers, supervisors and students. Data collection is done through interview, observation, and documentation. Data analysis using qualitative analysis technique. The results showed that the management of physics learning class at Public Senior High School Number 1 West Pendopo Empat Lawang Regency was conducted by physics teacher with the main objective so that the physics learning given to the students was really mastered by them as well as possible. Such mastery both in the meaning of conceptual mastery, as well as mastery of knowledge about physics in general. In order to get there the teacher first examines the main characteristics that are the essential elements of physics learning are believed to be very different from other fields of learning. The lesson of physics has its own identity, therefore the management of the classes done in the study of physics must be adapted to the main characteristics of the physics lesson itself